2023
DOI: 10.1136/bmjqs-2022-015538
|View full text |Cite
|
Sign up to set email alerts
|

Consent and refusal of procedures during labour and birth: a survey among 11 418 women in the Netherlands

Marit Sophia Gerardina van der Pijl,
Margot Klein Essink,
Tineke van der Linden
et al.

Abstract: BackgroundInformed consent for medical interventions is ethically and legally required; an important aspect of quality and safety in healthcare; and essential to person-centred care. During labour and birth, respecting consent requirements, including respecting refusal, can contribute to a higher sense of choice and control for labouring women. This study examines (1) to what extent and for which procedures during labour and birth women report that consent requirements were not met and/or inadequate informatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 47 publications
2
12
0
1
Order By: Relevance
“…The participants, both mothers and midwives, say mothers often do not know that they can refuse vaginal examinations, neither do they know that their regular performance is a highly contested and often not evidence-based intervention [ 39 ]. While only 7% of participants in Van der Pijl’s research lists that were not asked for consent for vaginal examinations, 60% of those who refused the examination said that their refusal was overruled [ 6 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The participants, both mothers and midwives, say mothers often do not know that they can refuse vaginal examinations, neither do they know that their regular performance is a highly contested and often not evidence-based intervention [ 39 ]. While only 7% of participants in Van der Pijl’s research lists that were not asked for consent for vaginal examinations, 60% of those who refused the examination said that their refusal was overruled [ 6 ].…”
Section: Resultsmentioning
confidence: 99%
“…Two quantitative studies on obstetric violence were conducted in the Netherlands based on one survey in which approximately 13.000 people participated [ 5 , 6 ]. 54.4% of respondents reported at least one form of disrespect and abuse.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 L’absence de demande de consentement n’est pas propre aux pays pauvres: une étude récente aux Pays-Bas a montré que le consentement pour administrer de l’ocytocine en postpartum ou pratiquer une épisiotomie n’était pas demandé dans 47.5% et 41.7% des cas respectivement. 28 Or, le manque de consentement aux soins est non seulement un aspect important des soins centrés sur le patient mais est aussi un facteur souvent mentionné par les femmes pour expliquer leur expérience traumatisante de l’accouchement. 29 Bien que le consentement soit exigé par l’article 58 du règlement intérieur des hôpitaux au Maroc, 30 34% des prestataires ont affirmé que le consentement des femmes avant les soins n’est pas toujours nécessaire .…”
Section: Discussionunclassified
“…13 The absence of a request for consent is not exclusive to low-income countries: a recent study in the Netherlands showed that consent for administering oxytocin postpartum or performing an episiotomy was not requested in 47.5% and 41.7% of cases, respectively. 28 However, the lack of informed consent is not only a crucial aspect of patient-centred care but is also frequently cited by women to explain their traumatic childbirth experience. 29 Even though consent is required by Article 58 of the internal regulations of hospitals in Morocco, 30 34% of providers stated that women’s consent before care is not always necessary.…”
Section: Discussionmentioning
confidence: 99%